Clinical and Laboratory Presentation and Underlying Mechanism in Patients with Low VWF - Seidizadeh, Omid; Ciavarella, Alessandro; Baronciani, Luciano; Boggio, Federico; Ballardini, Francesco; Cozzi, Giovanna; Colpani, Paola; Pagliari, Maria Teresa; Novembrino, Cristina; Siboni, Simona Maria; Peyvandi, Flora (Thrombosis and Haemostasis, 2023)
Background Low von Willebrand factor (VWF) refers to subjects with plasma levels of 30 to 50 IU/dL. The mechanism of low VWF is poorly understood. We chose to determine the clinical presentation, laboratory phenotype, and underlying mechanisms of low VWF.Material and Methods We included 250 patients characterized with low VWF. The International Society on Thrombosis and Haemostasis Bleeding Assessment Tool (ISTH-BAT) was used to assess clinical symptoms. To determine the underlying mechanisms of low VWF, we used as markers the VWF propeptide (VWFpp) assay and FVIII:C/VWF:Ag ratio for VWF synthesis and the VWFpp/VWF:Ag ratio for VWF clearance. Results were compared with those of 120 healthy controls. Cases with abnormal screening tests were further evaluated for coagulation factor levels and platelet disorders.Results The median age of the cohort was 35 years (range 3–85), 21% were children (n = 53), 34% were adult males (n = 85), and 45% (n = 112) were adult females. According to the ISTH-BAT, abnormal bleeding was found in 35% of children, 47% of males, and 49% of females. No association was found between VWF activity levels and ISTH-BAT. Patients showed an overall decreased VWF synthesis/secretion and an enhanced VWF clearance was identified in 33% of them. In 89 patients (36%), there were other hemostasis-related defects, but there was no difference in the ISTH-BAT between the two groups.Conclusion Our findings indicate that reduced VWF synthesis/secretion and enhanced VWF clearance are major mechanisms of low VWF levels. Patients with low VWF have significant bleeding manifestations. While other hemostasis defects occurred together with low VWF, this combination did not exacerbate clinical symptoms.
Keywords: VWD; VWF; low VWF; ISTH-BAT